Repositioning legal logic in the civic education curriculum to build critical citizens - Yayuk Hidayah; Meiwatizal Trihastuti; Nita Maghfiratul Jannah (Education of Law Journal, 2025)
Rapid socio-political change and the spread of disinformation demand that Citizenship Education move beyond the rote memorisation of legal norms and instead foster citizens who are capable of critical legal reasoning. This article proposes the repositioning of legal logic as a key epistemic framework within the Citizenship Education curriculum so that learners do not only know what the law states, but also understand why and how law operates in practice. Using a juridical-normative approach combined with qualitative content analysis of curriculum documents, textbooks, and teaching guidelines, this study examines the extent to which dimensions of legal logic—such as deductive–inductive reasoning, juridical argumentation, the distinction between legality and legitimacy, and the assessment of justice in legal norms—are integrated into teaching and learning processes. The findings indicate that the curriculum and learning materials remain dominated by a descriptive-dogmatic approach that positions law as a fixed text rather than as a field of public rationality open to argumentative debate. The proposed repositioning involves a shift from normative pedagogy to critical-argumentative pedagogy by incorporating case analysis exercises, mock trials, and constitutional debates grounded in legal logic into students’ learning experiences. Theoretically, this article strengthens the bridge between legal theory and citizenship education theory, while practically it offers recommendations for curriculum developers, teachers, and education policymakers to design learning that cultivates citizens who are critical, reflective, and responsible both legally and ethically.